Lef Congenital Mesoblasti Nephroma in a Term Male Neonate: A Case Report - Rattan, Kamal Nain; Bansal, Shruti; Sharma, Vibha; Sharma, Nikhil; Garg, Deepak Kumar (Iranian Journal of Pediatric Surgery, 2017)
Congenital mesoblasticnephroma (CMN) is a benign and very rare renal tumor, typically occurring in utero or during infancy. We are reporting a very young case of left sided classical congenital mesoblasticnephroma in a full term, small for gestational age, male neonate; who was detected with left sided flank mass immediately after birth. The patient was managed successfully by total nephrectomy. The diagnosis of CMN-classical type was confirmed on histopathological examination.